2010
DOI: 10.1002/emmm.201000103
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the severity of neuroinflammation and demyelination by TLR‐ASK1‐p38 pathway

Abstract: Apoptosis signal-regulating kinase 1 (ASK1) is an evolutionarily conserved mitogen-activated protein kinase (MAPK) kinase kinase which plays important roles in stress and immune responses. Here, we show that ASK1 deficiency attenuates neuroinflammation in experimental autoimmune encephalomyelitis (EAE), without affecting the proliferation capability of T cells. Moreover, we found that EAE upregulates expression of Toll-like receptors (TLRs) in activated astrocytes and microglia, and that TLRs can synergize wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 131 publications
(126 citation statements)
references
References 48 publications
(70 reference statements)
4
122
0
Order By: Relevance
“…Apoptosis signal-regulating kinase 1 (ASK1) is a TLR-controlled kinase that is known to activate p38 MAPK. Deletion of ASK1 attenuated p38 MAPK activation, EAE severity, and production of proinflammatory cytokines by astrocytes and microglia without affecting peripheral T cell responses, suggesting that ASK1-dependent activation of p38 MAPK glial cells may promote EAE pathogenesis (61). Taken together, these results suggest that p38 MAPK in CNS resident cells likely promotes EAE pathogenesis, but future studies are needed to show this definitively.…”
Section: The Role Of P38 Mapk Signaling In Cns-resident Cells In Eaementioning
confidence: 89%
“…Apoptosis signal-regulating kinase 1 (ASK1) is a TLR-controlled kinase that is known to activate p38 MAPK. Deletion of ASK1 attenuated p38 MAPK activation, EAE severity, and production of proinflammatory cytokines by astrocytes and microglia without affecting peripheral T cell responses, suggesting that ASK1-dependent activation of p38 MAPK glial cells may promote EAE pathogenesis (61). Taken together, these results suggest that p38 MAPK in CNS resident cells likely promotes EAE pathogenesis, but future studies are needed to show this definitively.…”
Section: The Role Of P38 Mapk Signaling In Cns-resident Cells In Eaementioning
confidence: 89%
“…Recent studies showed compound K811, a specific ASK1 inhibitor, had a beneficial effect on glial cell activation in experimental autoimmune encephalomyelitis 31 and gastric cancer cell growth in vitro and in vivo. 32 In the present study, administration of compound K811 mimicked the protective effects of ASK1 deficiency in the BCAS mice model.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 As Dock3 protects RGCs from oxidative stress, the combination of Dock3 overexpression and inhibition of ASK1 signaling by a specific inhibitor 42 may be further available for the management of glaucoma. One important point is that glaucoma is a complex disease resulting from the confluence of various factors.…”
Section: -37mentioning
confidence: 99%